2021
DOI: 10.1177/21514593211024509
|View full text |Cite
|
Sign up to set email alerts
|

Hip Fractures in the Elderly During the COVID-19 Pandemic: A Latin-American Perspective With a Minimum 90-Day Follow-Up

Abstract: Introduction: Hip fracture patients have been severely affected by the COVID-19 pandemic; however, the sub acute effects of a concomitant SARS-CoV-2 infection and the outcomes in highly exposed developing countries are still unknown. Our objective is to describe the morbidity and mortality of elderly patients admitted for a hip fracture during the COVID-19 pandemic in Chile, with a minimum 90-day follow-up. Also, to elucidate predictors for mortality and to compare mortality results with the pre-pandemic era. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
7
0
2
Order By: Relevance
“…By way of example, the rate of UTI in our study compared between the pre-pandemic and pandemic periods was 27 (13.7%) versus 64 (22.3%) ( p = 0.024). Our overall rate of UTI was 18.8%, which is comparable with the rates reported from previous studies (range, 8.3–24.0%) [ 23 , 38 40 ]. At our center, we do not routinely record the duration that an indwelling urinary catheter is retained; however, our hip fracture protocol during both the pre-pandemic and pandemic periods was to remove a urinary catheter on postoperative day 2 or when the hip fracture patient can ambulate out of bed.…”
Section: Discussionsupporting
confidence: 90%
“…By way of example, the rate of UTI in our study compared between the pre-pandemic and pandemic periods was 27 (13.7%) versus 64 (22.3%) ( p = 0.024). Our overall rate of UTI was 18.8%, which is comparable with the rates reported from previous studies (range, 8.3–24.0%) [ 23 , 38 40 ]. At our center, we do not routinely record the duration that an indwelling urinary catheter is retained; however, our hip fracture protocol during both the pre-pandemic and pandemic periods was to remove a urinary catheter on postoperative day 2 or when the hip fracture patient can ambulate out of bed.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, patients who experienced hip fragility fractures in the 2020 pandemic had a greater mortality compared to the same period of the pre-pandemic era [ 65 , 66 ]. COVID infection directly contributed to increase the 30- and 90-day mortality following fragility hip fractures, not explained by patient characteristics [ 67 70 ]. Moreover, a longer time span from injury to surgical treatment and a longer hospitalisation was evidenced in comparison to the preceding year 2019, when the pandemic began [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher mortality rate has been described in older individuals infected with COVID-19 [ 4 ]. In several studies, early mortality at 30 and 90 days increased significantly [ 1 , 3 ] between 30 and 60% according to different published series [ 4 , 21 , 24 , 25 ]. In a Spanish multicenter study [ 24 ], the hip fracture mortality rate observed at a mean follow-up of 14 days was higher than the 30-day mortality rate reported by the Spanish National Hip Fracture Registry and in the Swedish national fracture registry.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization declared the COVID-19 infection a global pandemic on March 11, 2020, and Latin America, in particular, became the most affected geographic area in the world in June 2020 [ 1 ]. The COVID-19 pandemic has disproportionately affected older adults, who, due to their frailty and associated comorbidities, proved to be the most vulnerable affected population; thus, the hospitalized elderly accounted worldwide for almost half of the deaths due to COVID-19 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%